Weather-resistant multi-layer co-extrusion automobile paint surface self-adhesion factory protection film

The weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film developed through multi-layer co-extrusion technology solves the health, environmental and weather resistance problems existing in the production and use of existing protective films, and realizes the application in open-air environments. Effectively protect car paint.

CN119331525APending Publication Date: 2025-01-21FELKER FUNCTIONAL MATERIALS (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411520581.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing automotive paint protective films have problems such as ozone emissions, harmful to workers' health, high solvent volatility, flammability and polluting the environment during the production process, and are not weather-resistant, making it difficult to effectively protect the automotive paint in an open-air environment.

Method used

Adopting a multi-layer co-squeezing technology to develop a weather resistance multi-layer and jointly squeezing car paint surface self-sticking factory protective film, including the surface, middle and adhesive, through polypropylene, titanium pink powder, anti-ultraviolet female granules, ethylene-α olefins The combination of co -concentrations and other materials improves the weather tolerance and adhesion of the membrane.

Benefits of technology

This protective film can effectively protect the paint surface of the vehicle under high temperature and high humidity environment, reduce ozone emissions and solvents volatilization, improve workers' safety, and maintain good adhesion capabilities at extremely low temperatures. It is suitable for open -air transportation and storage. car.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331525A_ABST
    Figure CN119331525A_ABST
Patent Text Reader

Abstract

The invention discloses a weather-resistant multi-layer co-extrusion automobile paint surface self-adhesive factory protection film which comprises a surface layer, a middle layer and an adhesive layer, anti-ultraviolet master batches are added into the surface layer and the middle layer, each anti-ultraviolet master batch is composed of PP, 10% of an ultraviolet light absorber, 10% of a light stabilizer and 0.2% of an anti-aging agent, and the adhesive layer is composed of PIB, SIBS, hydrogenated terpene phenolic resin, fumed silica and an antioxidant, however, active free radicals are generated in the process to destroy the existing molecular chain, so that the light stabilizer UV622 is added to prevent free radical destruction, and the weather resistance of the film is further improved. The SIBS in the adhesive layer is suitable for being used as an adhesive layer main material of a self-adhesive material due to the low TG temperature of-61 DEG C to-69 DEG C and excellent cohesive strength, and the adhesive tape made of the SIBS as the main material can adapt to use in cold regions, can still keep good adhesive capacity at the extremely low temperature, is free of residues and is easy to uncover.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of protective films, and in particular to a weather-resistant multi-layer co-extruded self-adhesive protective film for automobile paint surfaces. Background Art

[0002] Since the birth of automobiles, finished cars are generally not sold directly to consumers from factories, but are first distributed to various automobile 4S stores, and then 4S stores sell different models of cars to consumers. With the improvement of people's living standards, the demand for family cars has increased significantly, and there are more and more car styles. The process of transporting cars from factories to 4S stores for sale and in 4S store parking lots are generally mostly open-air. Especially in high-temperature and high-humidity open-air environments such as import and export ocean transportation, light, rain, bird droppings, etc. will have a relatively large negative impact on the paint. The A-pillar, B-pillar and pedals of the car are also easily scratched to varying degrees by test driving, manual opening and closing of the car door, etc., which will affect the sales appearance. In severe cases, it is even necessary to repaint in advance to maintain the overall beauty and integrity of the vehicle.

[0003] At present, the automotive paint protection films used in the existing process are almost all products made by the coating method. First, the substrate is made, and then the coating is done. The film corona process in this process will produce a large amount of ozone, which is easy to damage the atmosphere and the eyes and lungs of the workshop workers. The solvent used in the coating process is also a highly volatile gas, flammable and polluting the environment. In addition, the defects in the corona and coating process often cause the glue to fall off, which is extremely difficult to clean and easily pollutes the surface of the car. In this process, the edge materials cannot be recycled and used, and the loss in the secondary processing process is relatively high. The production process of this type of weather-resistant substrate and high-end glue are almost all in the hands of foreign manufacturers (placed outdoors for more than 12 months), resulting in the lack of domestically produced protective films that can be safely used in the automotive process in China.

[0004] Therefore, how to provide a weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film to solve the problems existing in the prior art is of great significance to its application. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide a weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film to solve the obvious shortcomings of traditional protective films.

[0006] To achieve the above object, the present invention provides the following technical solutions: a weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film, comprising a surface layer, a middle layer and an adhesive layer;

[0007] The surface layer is composed of polypropylene, titanium dioxide masterbatch, anti-ultraviolet masterbatch, and unwinding masterbatch;

[0008] The middle layer is composed of polypropylene, titanium dioxide masterbatch, anti-ultraviolet masterbatch, and ethylene-α-olefin copolymer;

[0009] The adhesive layer is composed of PIB, SIBS, hydrogenated terpene phenolic resin, fumed silica and antioxidant.

[0010] Preferably, the titanium dioxide masterbatch is composed of 17.8 components of PP, 80 components of rutile titanium dioxide, 2 components of polypropylene wax, and 0.2 components of anti-aging agent;

[0011] The anti-ultraviolet masterbatch is composed of 79.8% PP, 10% ultraviolet absorber, 10% light stabilizer and 0.2% anti-aging agent;

[0012] The decoiling masterbatch is ETFE masterbatch.

[0013] Preferably, the component ratio of the surface layer is: polypropylene 76-88%, titanium dioxide masterbatch 6-13%, anti-ultraviolet masterbatch 3%, and unwinding masterbatch 3-8%.

[0014] Preferably, the proportion of the middle layer components is: 85.5-87.5% polypropylene, 6% titanium dioxide masterbatch, 1.5% anti-ultraviolet masterbatch, and 3-7% ethylene-α-olefin copolymer.

[0015] Preferably, the component ratio of the adhesive layer is: 5-8 components of PIB, 78.5-85.5 components of SIBS, 8-15 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 component of antioxidant.

[0016] Preferably, in the anti-ultraviolet masterbatch and anti-ultraviolet masterbatch: the rutile titanium dioxide is used to effectively block sunlight; the ultraviolet absorber is used to absorb ultraviolet rays, prevent or weaken the redox effect of ultraviolet light chemistry, and prevent color degradation; the light stabilizer adopts UV-622, and the light stabilizer is used to neutralize destructive free radicals; the ethylene-α-olefin copolymer is used to reduce the film peeling sound and increase the dispersion effect of titanium dioxide; the anti-aging agent is used to prevent aging during the physical heating process, and the fumed silica is used for anti-sticking, filling, and improving the temperature resistance of the adhesive layer.

[0017] Preferably, the anti-ultraviolet masterbatch and anti-ultraviolet masterbatch are made into masterbatch by using a twin-screw granulator to make the above titanium dioxide and anti-ultraviolet components into masterbatch in proportion, with a high shear and high mixing screw with a length-to-diameter ratio of 48 or more and a screw diameter of not less than 65mm, and are processed and formed at a temperature of 160-180 degrees for standby use.

[0018] Preferably, all the formula materials of the adhesive layer are granulated by a twin-screw granulator, the screw diameter is 65 mm, the aspect ratio is greater than 60, the granulation temperature is 180-220 degrees, 0.5% of the fumed silica is mixed in the granulation, and the remaining 0.5% is sprinkled on the molded particles as an anti-sticking release agent to obtain an adhesive layer masterbatch.

[0019] Preferably, the protective film is produced by a 1600mm wide three-layer mold composite special casting equipment, the mouth mold adopts a 1.0-2.0mm automatic mold, the screw diameter is: 50mm / 80mm / 50mm, the casting cooling roller is preferably a matte roller with a surface roughness of 0.2um, and the roller on the side of the cooling roller that contacts the rubber layer is treated with anti-slip treatment.

[0020] Preferably, in the three-layer mold internal composite special casting equipment, the surface layer processing temperature is 245 degrees, the middle layer processing temperature is 240 degrees, the adhesive layer processing temperature is 220 degrees, the mold temperature is 245 degrees, the surface layer thickness is 9um, the middle layer thickness is 36um, the adhesive layer thickness is 5um, the total product thickness is 50um, and it is rolled up.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. SIBS in the adhesive layer of the present invention is suitable as the main material of the adhesive layer of the self-adhesive material because of its low TG temperature of -61 to -69 and relatively high cohesive strength. PIB has its own cold flow effect and can better wet the surface. After being added, the adhesive layer can be further softened, so that the bonding process has a better bonding effect for arcs or bends. The hydrogenated terpene phenolic resin has a slight polarity and can well give the tape better adhesion. The tape made of SIBS as the main material can adapt to the use in cold areas, and can still maintain good adhesion at extremely low temperatures, without floating, and is easy to peel off.

[0023] 2. In the middle layer and the surface layer of the present invention, the anti-ultraviolet masterbatch is used to absorb ultraviolet rays, prevent or weaken the redox effect of ultraviolet light chemistry, and prevent color degradation. The ethylene-α-olefin copolymer can make the film peeling off silent and make the film soft, so that it can be smoothly attached to the arc position without warping. At the same time, it can increase the dispersion effect of titanium dioxide in the film, making it more uniform. The gas phase silica is used for anti-sticking and filling, and the temperature resistance of the adhesive layer is improved.

[0024] 3. In the middle layer and the surface layer of the present invention, titanium dioxide is responsible for shielding light, and the ultraviolet absorber 531 inside can absorb excess ultraviolet rays, but it will produce free radicals to destroy the existing molecular chains, so the light stabilizer 622 is used to prevent free radical damage, thereby improving the weather resistance of the substrate.

[0025] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application so that it can be implemented in accordance with the contents of the specification, and to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the following is a detailed description of the preferred embodiments of the present application in conjunction with the accompanying drawings as follows.

[0026] Based on the detailed description of the specific embodiments of the present application in combination with the accompanying drawings below, those skilled in the art will become more aware of the above and other objects, advantages and features of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can also be obtained based on these drawings without creative work. In all drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.

[0028] Figure 1 This is a table of the composition contents of the present invention.

[0029] Figure 2 This is a table of embodiments of the substrate layer in the present invention;

[0030] Figure 3 This is a table of embodiments of the adhesive layer of the present invention;

[0031] Figure 4 This is a table of test results of the adhesive layer in the present invention. DETAILED DESCRIPTION

[0032] To make the purpose, technical scheme and advantages of the embodiment of the present application clearer, the technical scheme in the embodiment of the present application will be clearly and completely described below in conjunction with the accompanying drawings in the embodiment of the present application. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all of the embodiments. In the following description, specific details such as specific configuration and components are provided only to help fully understand the embodiments of the present application. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present application. In addition, for clarity and brevity, the description of known functions and structures is omitted in the embodiment.

[0033] In addition, the present application may repeat reference numerals and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not in itself indicate the relationship between the various embodiments and / or settings discussed.

[0034] The term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, B exists alone, and A and B exist at the same time. The term " / and" in this article describes another type of association object relationship, indicating that there can be two relationships. For example, A / and B can mean: A exists alone, and A and B exist alone. In addition, the character " / " in this article generally indicates that the previous and next associated objects are in an "or" relationship.

[0035] It should also be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusions.

[0036] See also Figure 1-3 The present invention provides a technical solution for a weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film:

[0037] The substrate layer includes the surface layer and the middle layer

[0038] Example 1: The proportion of the surface layer components: 88% polypropylene (PP), 6% titanium dioxide masterbatch, 3% anti-ultraviolet masterbatch, and 3% unwinding masterbatch; the proportion of the middle layer components includes: 87.5% polypropylene, 6% titanium dioxide masterbatch, 1.5% anti-ultraviolet masterbatch, and 3% ethylene-α-olefin copolymer;

[0039] Example 2: The proportion of the surface layer components: polypropylene (PP) 88%, titanium dioxide masterbatch 6%, anti-ultraviolet masterbatch 3%, unwinding masterbatch 3-8%; the proportion of the middle layer components includes: polypropylene 87.5%, titanium dioxide masterbatch 6%, anti-ultraviolet masterbatch 1.5%, ethylene-α-olefin copolymer 3%;

[0040] Example 3: The proportion of the surface layer components: polypropylene (PP) 79%, titanium dioxide masterbatch 13%, anti-ultraviolet masterbatch 3%, unwinding masterbatch 5%; the proportion of the middle layer components includes: polypropylene 87.5%, titanium dioxide masterbatch 6%, anti-ultraviolet masterbatch 1.5%, ethylene-α-olefin copolymer 3%;

[0041] Example 4: The proportion of the surface layer components: polypropylene (PP) 77%, titanium dioxide masterbatch 13%, anti-ultraviolet masterbatch 3%, unwinding masterbatch 8%; the proportion of the middle layer components includes: polypropylene 87.5%, titanium dioxide masterbatch 6%, anti-ultraviolet masterbatch 1.5%, ethylene-α-olefin copolymer 5%;

[0042] Example 5: The proportion of the surface layer components: polypropylene (PP) 76%, titanium dioxide masterbatch 6-13%, anti-ultraviolet masterbatch 3%, unwinding masterbatch 3-8%; the proportion of the middle layer components includes: polypropylene 85.5%, titanium dioxide masterbatch 6%, anti-ultraviolet masterbatch 1.5%, ethylene-α-olefin copolymer 7%;

[0043] Selection of each component:

[0044] PP uses Hanhua BI30, titanium dioxide: DuPont R902, UV absorber: BASF UV-531, ethylene-alpha olefin copolymer: DOW, 0203, polypropylene wax: Clariant 2502; anti-aging agent: BASF 1010; fumed silica: Evonik A380PIB BASF OPPANOL series B15, SIBS: Zhongyuan SIBSTAR series 062T, hydrogenated terpene phenolic resin: Japan Yasuhara, TH-130, fumed silica, unwinding masterbatch is ETFE masterbatch, using ETFE masterbatch makes the overall film have better unwinding effect, and at the same time makes the overall film able to prevent acid rain, and increase the weather resistance of the overall film.

[0045] The film is formed by T-type cast co-extrusion method. The overall film processing temperature range is 220-245 degrees, the cooling roller temperature is 25 degrees, the film surface layer accounts for 20%, the middle layer accounts for 80%, and the thickness is 45um.

[0046] Cast film equipment is generally single-screw equipment with an upper limit on its dispersion capacity. When titanium dioxide masterbatch is added to 13% (the actual content of titanium dioxide in a single layer is 10% as the upper limit), the film appears slightly rough, but it is still within the range. After POE is added to the middle layer, the proportion reaches 7%, which makes the film curled, and 3% POE does not disperse titanium dioxide as well as 5%. The unwinding effect was tested with 3M's 7475 tape and found that the unwinding force effects of 5% and 8% are basically the same, and will not become easier with the increase of content. The film surface effects of all materials are good.

[0047] Weathering test: Reference standard: Air corrosion resistance GB / T16422-1 23 (equivalent to ISO4892, simulated outdoor 12-month test environment, and then the material was tested for colorimetry on the back side to observe whether there were cracks, spots, etc., and then the mechanical properties of the film were tested with a tensile machine. Considering the comprehensive cost and other factors, Example 3 was preferred as the substrate layer of this protective film.

[0048] Then there is the choice of the self-adhesive layer;

[0049] Adhesive Example 1: 85.5 components of SIBS, 5 components of PIB, 8 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, 0.5 components of antioxidant;

[0050] Adhesive Example 2: 83.5 components of SIBS, 5 components of PIB, 10 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 components of antioxidant;

[0051] Adhesive Example 3: 78.5 components of SIBS, 5 components of PIB, 15 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 components of antioxidant;

[0052] Adhesive Example 4: 85.5 components of SIBS, 8 components of PIB, 8 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 components of antioxidant;

[0053] Adhesive Example 5: 83.5 components of SIBS, 8 components of PIB, 10 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 components of antioxidant;

[0054] Adhesive Example 6: 78.5 components of SIBS, 8 components of PIB, 15 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 components of antioxidant;

[0055] Adhesive Example 7: 85.5 components of SIBS, 10 components of PIB, 8 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 components of antioxidant;

[0056] Adhesive Example 8: 83.5 components of SIBS, 10 components of PIB, 10 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 components of antioxidant;

[0057] Adhesive Example 9: 18.5 components of SIBS, 10 components of PIB, 15 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 component of antioxidant;

[0058] The processing temperature of the adhesive layer is 225 degrees. Example 3 is used as the substrate. The overall self-adhesive film thickness is 50um, the surface layer thickness is 9um, the middle layer thickness is 36um, and the adhesive layer thickness is 5um.

[0059] The test items include: unfolding force, initial adhesion, adhesion after high temperature, contamination, and film curling test.

[0060] (1) Development force

[0061] The surface protection film was wound on a PP tube core with an inner diameter of 3 inches to make a film roll with a width of 50 mm. According to JIS Z0237, the surface protection film was unwound from the film roll at an unwinding speed of 20 m / min, and the high-speed unwinding force was measured. The test value is the unfolding force;

[0062] Internal standard: The unfolding force of 1N / 50mm is evaluated as A, the one exceeding 1N / mm but not exceeding 2N / 50mm is evaluated as B, and the one exceeding 2N / 50mm is evaluated as C.

[0063] (2) Initial adhesion

[0064] The surface protection film was laminated 72 hours after it was made. A special magnetic paint was prepared, and pearlescent powder (metal chips) was added during spraying. The front cover of the "2019 BYD Qin" car, also known as metallic paint, was cut into 15cmX5cm test plates. The lamination conditions were at room temperature of 23 degrees and relative humidity of 50%. A 2kg rubber roller was used to laminate at a speed of 300mm / min. After leaving it in this state for 30 minutes, the 180-degree peel strength of 25mm width was tested at a speed of 300mm / min according to JIS Z0237. The peel strength at this time is taken as the initial adhesion.

[0065] (3) Adhesion after high temperature

[0066] The surface protection film was laminated 72 hours after it was made. A special magnetic paint was prepared, and pearlescent powder (metal chips) was added during spraying. The front cover of the "2019 BYD Qin" car, also known as metallic paint, was cut into test plates of 15cmX5cm size. The lamination conditions were at room temperature of 23 degrees and relative humidity of 50%. A 2kg rubber roller was used to laminate at a speed of 300mm / min. After being placed in this state for 30 minutes, the laminated product was placed at a temperature of 90 degrees for 30 minutes for baking. After baking, it was taken out and allowed to stand for 30 minutes. Then, the 180-degree peel strength of 25mm width was tested at a speed of 300mm / min according to JIS Z0237. The peel strength at this time is used as the adhesion after high temperature.

[0067] (4) Weathering resistance test;

[0068] Reference standard: Air corrosion resistance GB / T16422-123 (equivalent to ISO4892, put the cover with protective film into the xenon lamp aging test box, test for 1000 hours to simulate the outdoor 12-month test environment, then compare the color of the material on the back side to observe whether there are cracks, spots, etc., and then peel off the film to observe whether it can be peeled off completely

[0069] (5) Pollution

[0070] After peeling off the sample film from the adhered object, spotlight the adhered surface in a dark room and observe the surface contamination status with the naked eye. The status is determined as follows: no contamination A, slight contamination B, contamination C

[0071] Test results:

[0072] (1) The results of the room temperature peeling force test for adhesive samples 1-9 were 1N / 25mm, 1.2N / 25mm, 1.5N / 25mm, 0.8N / 25mm, 1.0N / 25mm, 2.0N / 25mm, 1.5N / 25mm, 2.0N / 25mm, and 3.0N / 25mm, respectively;

[0073] (2) The peeling force test results after high temperature were 2.1 N / 25 mm, 2.7 N / 25 mm, 3.5 N / 25 mm, 1.9 N / 25 mm, 2.1 N / 25 mm, 3.9 N / 25 mm, 2.6 N / 25 mm, 3.5 N / 25 mm, and 6.0 N / 25 mm for adhesive samples 1 to 9, respectively;

[0074] (3) Contamination test results: Grade A: sticky examples 1, 2, 4, 5; Grade B: sticky example 7; Grade C: sticky examples 3, 6, 8, 9;

[0075] (4) Curl test results: Grade A: sticky examples 3, 4, and 5; Grade B: sticky examples 1, 6, 7, 8, and 9;

[0076] (5) Development force test results: Grade A: sticky examples 1, 2, 4, 5, 6; Grade B: sticky examples 3, 7, 8, 9;

[0077] (6) Weathering resistance test results: Examples 1-9 all had spots and cracks, and all could be peeled off in one piece.

[0078] After comprehensive evaluation, Example 3 is the preferred choice.

[0079] The test found that when the content of hydrogenated terpene phenolic resin in this formula system exceeds 10%, precipitation occurs in a high temperature environment. PIB content exceeds 8% and is also very easy to precipitate. From the perspectives of viscosity, unwinding, residue, etc., the adhesive layer preferably adopts Scheme 5. The film made with substrate 3 can meet the requirements in terms of weather resistance and bonding effect.

[0080] The above description is only the preferred embodiment of the present invention, which does not limit the protection scope of the present invention. For those skilled in the art, the present invention can be modified and varied in various ways. Within the spirit and principle of the present invention, any change, modification, replacement, integration and parameter change of these embodiments by conventional substitution or capable of achieving the same function without departing from the principle and spirit of the present invention shall fall within the protection scope of the present invention.

Claims

1. A weather-resistant multi-layer co-extruded self-adhesive protective film for automobile paint, characterized in that: It includes the surface layer, the middle layer and the sticky layer; The surface layer is composed of polypropylene, titanium dioxide masterbatch, anti-ultraviolet masterbatch, and unwinding masterbatch; The middle layer is composed of polypropylene, titanium dioxide masterbatch, anti-ultraviolet masterbatch, and ethylene-α-olefin copolymer; The adhesive layer is composed of PIB, SIBS, hydrogenated terpene phenolic resin, fumed silica and antioxidant.

2. A weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film as claimed in claim 1, characterized in that: The titanium dioxide masterbatch is composed of 17.8 components of PP, 80 components of rutile titanium dioxide, 2 components of polypropylene wax, and 0.2 components of anti-aging agent; The anti-ultraviolet masterbatch is composed of 79.8% PP, 10% ultraviolet absorber, 10% light stabilizer and 0.2% anti-aging agent; The decoiling masterbatch is ETFE masterbatch.

3. A weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film as claimed in claim 2, characterized in that: The component ratios of the surface layer are: polypropylene 76-88%, titanium dioxide masterbatch 6-13%, anti-ultraviolet masterbatch 3%, and unwinding masterbatch 3-8%.

4. A weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film as claimed in claim 3, characterized in that: The proportions of the middle layer components are: 85.5-87.5% of polypropylene, 6% of titanium dioxide masterbatch, 1.5% of anti-ultraviolet masterbatch, and 3-7% of ethylene-alpha olefin copolymer.

5. A weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film as claimed in claim 4, characterized in that: The component ratio of the adhesive layer is: 5-8 components of PIB, 78.5-85.5 components of SIBS, 8-15 components of hydrogenated terpene phenolic resin, 1 component of fumed silica, and 0.5 component of antioxidant.

6. A weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film as claimed in claim 5, characterized in that: In the anti-ultraviolet masterbatch and anti-ultraviolet masterbatch: the rutile titanium dioxide is used to effectively block sunlight; the ultraviolet absorber is used to absorb ultraviolet rays, prevent or weaken the redox effect of ultraviolet light chemistry, and prevent color degradation; the light stabilizer adopts UV-622, and the light stabilizer is used to neutralize destructive free radicals; the ethylene-α-olefin copolymer is used to reduce the film peeling sound and increase the dispersion effect of titanium dioxide; the anti-aging agent is used to prevent aging during the physical heating process, and the fumed silica is used for anti-sticking, filling, and improving the temperature resistance of the glue layer.

7. A weather-resistant multi-layer co-extruded self-adhesive automotive paint surface protective film as claimed in claim 6, characterized in that: The anti-ultraviolet masterbatch and anti-ultraviolet masterbatch use a twin-screw granulator to make the above titanium dioxide and anti-ultraviolet components into masterbatch according to proportion. The screw adopts a high-shear high-mixing screw with a length-to-diameter ratio of more than 48, and the screw diameter is not less than 65mm. It is processed and formed at a temperature of 160-180 degrees for standby use.

8. A weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film as claimed in claim 7, characterized in that: All the formula materials of the adhesive layer are granulated by a twin-screw granulator. The screw diameter is 65 mm, the aspect ratio is greater than 60, and the granulation temperature is 180-220 degrees. 0.5% of the fumed silica is mixed in the granulation, and the remaining 0.5% is sprinkled on the molded particles as an anti-sticking release agent to obtain an adhesive layer masterbatch.

9. A weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film as claimed in claim 8, characterized in that: The protective film is produced by a 1600mm wide three-layer mold composite special casting equipment, the mouth mold adopts a 1.0-2.0mm automatic mold, the screw diameter is: 50mm / 80mm / 50mm, the casting cooling roller is preferably a matte roller with a surface roughness of 0.2um, and the roller on the side of the cooling roller that contacts the rubber layer is anti-slip treated.

10. A weather-resistant multi-layer co-extruded automobile paint self-adhesive factory protective film as claimed in claim 9, characterized in that: In the three-layer mold internal composite special casting equipment, the surface layer processing temperature is 245 degrees, the middle layer processing temperature is 240 degrees, the adhesive layer processing temperature is 220 degrees, the mold temperature is 245 degrees, the surface layer thickness is 9um, the middle layer thickness is 36um, the adhesive layer thickness is 5um, the total product thickness is 50um, and it is rolled.